Visionary Leadership in Improving the Quality of Students at the Al-Mujahadah Islamic Boarding School in Merangin, Jambi - Rosidi, Akhyar; Asy’ari, Hasyim; Aqraminas, Dayu (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
Visionary leadership is a leader who cares, namely by changing institutions from stagnation to an extraordinary innovative education system. Visionary leadership is a very important approach in improving the quality of students at the Al-Mujahadah Islamic Boarding School. Islamic boarding schools as Islamic educational institutions need leaders who are able to provide long-term direction and vision to achieve better educational goals. This research aims to explore how visionary leadership can contribute positively to improving the quality of students at the Al-Mujahadah Islamic Boarding School. The research method used is qualitative with a case study approach. Data was collected through interviews, observation and analysis of related documents. The research results show that the visionary leadership implemented by the Al-Mujahadah Islamic Boarding School administrators has had a positive impact on the development and quality of the students. This visionary leadership is reflected in establishing a clear vision and mission, fostering creativity, and implementing learning programs that are relevant to the needs of students. The application of visionary leadership also creates an inclusive and supportive Islamic boarding school environment, motivating students to develop academic, social and spiritual potential. Apart from that, the success of the Islamic boarding school in achieving the goals of Islamic education is also proof of the effectiveness of the visionary leadership implemented at Al-Mujahadah Islamic Boarding School. In conclusion, visionary leadership at Al-Mujahadah Islamic Boarding School is able to make a significant contribution in improving the quality of students. Implementing a long-term vision, fostering creativity and contextual learning are the keys to success in forming quality students who are able to face the challenges of the times.